2021
DOI: 10.1111/cns.13623
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term music adjuvant therapy enhances the efficacy of sub‐dose antiepileptic drugs in temporal lobe epilepsy

Abstract: Aims Noninvasive music adjuvant therapy shows great potential in improving seizure control when combined with routine antiepileptic drugs. However, the diversity of previous music protocols has resulted in disparate outcomes. The optimized protocol and features for music adjuvant therapy are still not fully understood which limits its feasibility. Methods By applying different regimens of music therapy in various temporal lobe epilepsy models, we evaluated the effect of music in combination with sub‐dose drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…As early as more than 2200 years ago, the view of “five‐tone therapy for diseases” was put forward in the Inner Canon of Huangdi. Xu et al found that Mozart K.448 adjuvant therapy combined with different sub‐dose ASMs can alleviate seizure severity in temporal lobe epilepsy models and the therapeutic effect was related to the modulation of seizure electroencephalogram (EEG) spectral powers in the hippocampus 71 . A randomized controlled clinical trial found that children in the intervention group who were given Mozart K.448 for eight minutes once daily before bedtime for at least six months had a significantly lower seizure recurrence rate (p = 0.0109) and their EEG discharge also improved significantly after 2 years 72 .…”
Section: Resultsmentioning
confidence: 99%
“…As early as more than 2200 years ago, the view of “five‐tone therapy for diseases” was put forward in the Inner Canon of Huangdi. Xu et al found that Mozart K.448 adjuvant therapy combined with different sub‐dose ASMs can alleviate seizure severity in temporal lobe epilepsy models and the therapeutic effect was related to the modulation of seizure electroencephalogram (EEG) spectral powers in the hippocampus 71 . A randomized controlled clinical trial found that children in the intervention group who were given Mozart K.448 for eight minutes once daily before bedtime for at least six months had a significantly lower seizure recurrence rate (p = 0.0109) and their EEG discharge also improved significantly after 2 years 72 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous animal studies have suggested that music alleviates pain and improves social behaviors under various pathophysiological conditions [46][47][48][49]. In addition, it has been reported that music adjuvant therapy enhances the efficacy of antiepileptic drugs in various temporal lobe epilepsy models [46].…”
Section: Discussionmentioning
confidence: 99%
“…A promising DTx "active ingredient" for epilepsy is specific music [280,281,[296][297][298][299][300][301], and the clinical effects were also reproduced in preclinical studies [23,302,303]. Xu and colleagues showed that exposure of TLE mice to a specific music composition enhanced the anti-seizure activity of sub-effective doses of valproic acid or levetiracetam [303].…”
Section: Epilepsymentioning
confidence: 99%